User Education Practices for Effective Use of Library Resources and Services in Colleges of Education in Delta State, Nigeria - Afokewhre Henry Governor; Olanike Faith Mesagan (South Sulawesi Education Development (SSED), 2024)
The study explored user education practices for effective use of library resources in Delta state's colleges of education thereby addressing a significant gap, using a descriptive survey design with 400 students sampled from a total population of 9,979. Structured questionnaire was used and distributed by researchers with the assistance of two colleagues. assistance owing to proximity. Analysis include percentages, mean scores and standard deviation. Findings indicated insufficient user education provision, diverse delivery modes, lack of modern strategies and ineffective user education which hinders library service delivery. Recommendations include integrating modern strategies like podcasting and web 2.0 into the curriculum, organizing searching tools, mandating computer literacy courses, and conducting practical sessions, orientations, lectures, and seminars. The study concluded that embracing user education fully would foster better user-library relationships in Delta state's colleges of education. The implication is that with effective user education, students’ confusion on the use of library resources and how to navigate the holdings available in those libraries will be eradicated. It was recommended that for library staff to effectively use the resources and services available, user education should be their first concern.